Expedited Transition in the Wettability Response of Metal Meshes Structured by Femtosecond Laser Pulses for Oil-Water Separation - Khan, Sharjeel Ahmed; Ialyshev, Vadim; Kim, Vyacheslav V.; Iqbal, Mazhar; Al Harmi, Hamad; Boltaev, Ganjaboy S.; Ganeev, Rashid A.; Alnaser, Ali S. (Frontiers in Chemistry, 2020)
Oil-water separation using super-wetting and the selective permeability of membranes for oil or water has great ecological and economic significance. We report on the transition of wettability response, from superhydrophilic underwater-superoleophobic to superhydrophobic-superoleophilic state, by nanostructuring stainless steel and copper meshes using ultrashort femtosecond laser pulses. Our approach is environment-friendly, chemical free, and efficient as it exploits the benefit of aging the processed samples in a high vacuum environment. We optimized the laser scanning parameters, mesh pore size, and aging conditions to produce membranes exhibiting an extraordinary separation efficiency of 98% for the oil-water mixture. A variation in the water and oil contact angles for different meshes is presented as a function of the laser scanning speed. Stainless steel meshes with 150 μm pore size and copper meshes with 100 μm pore size have demonstrated an excellent wettability response for oil and water phases. Vacuum aging causes rapid chemisorption of hydrocarbons on laser-structured surfaces in the absence of water molecules, rapidly transforming the wetting state from superhydrophilic to superhydrophobic.